Acoustic modelling of machines using the inversion method for the purposes of the acoustic assessment of machines - PLEBAN, Dariusz (Archives of Acoustics, 2007)
Issues related to the development of acoustic models of machines are important factors both in the design of low-noise machines and in the prediction of machines noise. The acoustic modelling of machines may be carried out using a set of omni-directional substitute sound sources, located in points related to the functional elements of machines. The optimal parameters of these sources may be determined using an inversion method. To calculate these parameters by using the inversion method one must know the real distribution of sound pressure around the machine. This requires the determination, on the surface of hemisphere, of both the distribution of the amplitude of sound pressures, as well as the distribution of phase shift angles between acoustic signals. Computer simulations yield optimal parameters (sound power) for the individual omni-directional sound sources. Using the calculated parameters of the substitute sources it is possible to determine the radiation characteristics and to carry the acoustic assessment of the machine.